HIRADC Analysis for Rolling Stock Body Lifting Ngrombo Railway Maintenance Center - Wawan Riyanta (Civil Engineering Collaboration, 2023)
The Railway Maintenance Center as stated in the Regulation has the duty and function of carrying out the maintenance of state-owned railway facilities. The part of rolling stock heavy maintenance with high potential hazard is Lifting Body Activities Using OHTC in Maintenance of Hydraulic Diesel Locomotive Facilities activity. it so there is a need for a risk assessment which is a process to determine control priorities for the level of risk work accident or occupational disease. Part of OHSAS 18001:2007 Clouse 4.3.1. recommendation HIRADC methode for can support a safety system with 3 stage analisys (hazard identification, risk assessment, and control determination) The Hazard Identification results obtained 3 aspects of hazard risk in OHTC Rolling stock Body Lifting operations with the following analysis results Crane toppling, Equipment failure, Load falling with Death & asset / property damage impact factor. Risk Assessment analisys of Rolling stock Body Lifting using OHTC obtained results action taken when resources are available regarding handling which in general were Administrative Control. Determine Control relevant steps to minimize potential hazards immediately (1) Evaluating SOP Rolling stock Body Lifting and conduct outreach to all employees related to the work, (2) Making and or adding hazard signs and (3) Human development by conducting Training/Refreshment Crane Operator and Signal man. (4) Strictness of the rules for using PPE for all employees related to the work as the last step in minimizing the risk of occupational hazards.